South Asia subregional economic cooperation operational plan 2016-2025 update. ([Manila] Asian Development Bank, 2020)
This involves defining SASEC transport and energy networks and identifying priority projects based on preparedness and their roles in filling network gaps. The result is a more reasonable estimate of funding needs to help meet the SASEC Program goals of multimodal connectivity, energy market development, and increased intraregional and interregional trade.
Keywords: Public administration; South Asia; Electronic book